Facile Synthesis of Photofunctional Nanolayer Coatings on Titanium Substrates - Choi, Kyong-Hoon (Hindawi Publishing Corporation, 2016)
We developed a two-step chemical bonding process using photosensitizer molecules to fabricate photofunctional nanolayer coatings on hematoporphyrin- (HP-) coated Ti substrates. In the first step, 3-aminopropyltriethoxysilane was covalently functionalized onto the surface of the Ti substrates to provide heterogeneous sites for immobilizing the HP molecules. Then, HP molecules with carboxyl groups were chemically attached to the amine-terminated nanolayer coatings via a carbodiimide coupling reaction. The microstructure and elemental and phase composition of the HP-coated Ti substrates were investigated using field-emission scanning electron microscopy and energy-dispersive X-ray spectrometry. The photophysical properties of the photofunctional nanolayer coatings were confirmed using reflectance ultraviolet-visible absorption and emission spectrophotometry. The singlet oxygen generation efficiency of the photofunctional nanolayer coatings was determined using the decomposition reaction of 1,3-diphenylisobenzofuran. The HP-coated Ti substrates exhibited good biocompatibility without any cytotoxicity, and these nanolayer coatings generated singlet oxygen, which can kill microorganisms using only visible light.